Rationale and design of the Apixaban for the Reduction of Thrombo-Embolism in Patients With Device-Detected Sub-Clinical Atrial Fibrillation (ARTESiA) trial - Lopes, Renato D.; Alings, Marco; Connolly, Stuart J.; Beresh, Heather; Granger, Christopher B.; Mazuecos, Juan Benezet; Boriani, Giuseppe; Nielsen, Jens C.; Conen, David; Hohnloser, Stefan H.; Mairesse, Georges H.; Mabo, Philippe; et al. (The American heart journal, 2017)
Device-detected subclinical atrial fibrillation (AF) refers to infrequent, short-lasting, asymptomatic AF that is detected only with long-term continuous monitoring. Subclinical AF is common and associated with an increased risk of stroke; however, the risk of stroke with subclinical AF is lower than for clinical AF, and very few patients with subclinical AF alone have been included in large AF anticoagulation trials. The net benefit of anticoagulation in patients with subclinical AF is unknown. ARTESiA is a prospective, multicenter, double-blind, randomized controlled trial, recruiting patients with subclinical AF detected by an implanted pacemaker, defibrillator, or cardiac monitor, and who have additional risk factors for stroke. Patients with clinical AF documented by surface electrocardiogram will be excluded from the study. Participants will be randomized to receive either apixaban (according to standard AF dosing) or aspirin 81mg daily. The primary outcome is the composite of stroke, transient ischemic attack with diffusion-weighted magnetic resonance imaging evidence of cerebral infarction, and systemic embolism. Approximately 4,000 patients will be enrolled from around 230 clinical sites, with an anticipated mean follow-up of 36months until 248 adjudicated primary outcome events have occurred. ARTESiA will determine whether oral anticoagulation therapy with apixaban compared with aspirin reduces the risk of stroke or systemic embolism in patients with subclinical AF and additional risk factors.